NEW RECORDS IN THE FLORA CHECKLISTS OF LAOS, RESULTING FROM A SURVEY OF PHOU HIN POUN NATIONAL BIODIVERSITY CONSERVATION AREA - Prosperi, J.; Lamxay, V.; Hallé, F.; Bompard, J.-M.; Blanc, P.; Ramesh, B. R.; Ayyappan, N.; Cardinal, S. (Edinburgh Journal of Botany, 2017)
The flora of Laos remains one of the least known within the Indo-Burma biodiversity hotspot. A floristic inventory was carried out in Phou Hin Poun National Biodiversity Conservation Area, an under-explored area of the Khammouane Limestone. This study provides a list of 27 taxa that are additions to the most recent country checklists. The Ebenaceae, Euphorbiaceae and Myrtaceae are the families with the highest species number. In this list, four species are endemic to Indochina (Cambodia, Laos and Vietnam): Cynometra dongnaiensis Pierre, Jasminum vidalii P.S.Green, Memecylon chevalieri Guillaumin and Pothos gigantipes Buchet ex P.C.Boyce. These results illustrate the paucity of our knowledge of the region surveyed and of the flora of Laos in general.
Keywords: Additions; canopy access; endemics; forest; Khammouane Limestone; Laos; new records